2018
DOI: 10.7821/naer.2018.1.252
|View full text |Cite
|
Sign up to set email alerts
|

MOOCs and their Influence on Higher Education Institutions: Perspectives from the Insiders

Abstract: Since Massive Open Online Courses (MOOCs) became a global phenomenon in 2012, there has been constant evolution in the way Higher Education Institutions (HEIs) make sense of them. HEIs embracing MOOCs have dedicated a variety of human resource to this venture. Only in a minority of cases, staff have been appointed exclusively to this role. In all other cases, MOOC related tasks have been allocated to professionals who were already performing other educational tasks. This article contains a study that captures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The results of this study also support the claims of Dennis (2012), Yuan and Powell (2013), Iqbal et al (2014), Czerniewicz et al (2014), Schuwer et al (2015) and León-Urrutia et al (2018), among others, that MOOCs are not only favourable to the general public but also to students of higher education courses. This study has shown that the students of the undergraduate course English Pronunciation who successfully completed the LMOOC showed better results in their oral production than those who did not take the LMOOC and only worked with the regular course materials.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study also support the claims of Dennis (2012), Yuan and Powell (2013), Iqbal et al (2014), Czerniewicz et al (2014), Schuwer et al (2015) and León-Urrutia et al (2018), among others, that MOOCs are not only favourable to the general public but also to students of higher education courses. This study has shown that the students of the undergraduate course English Pronunciation who successfully completed the LMOOC showed better results in their oral production than those who did not take the LMOOC and only worked with the regular course materials.…”
Section: Discussionsupporting
confidence: 89%
“…MOOCs were conceived as free courses which required no entry qualifications and which were addressed to students of any age, nationality and social background ). This new system of online tuition reached wide audiences and was soon accepted as a valuable source of opportunities at individual, institutional, and social levels (León-Urrutia et al 2018). Even though one of the initial aims of MOOCs was to open education to a general public, recent research has shown that MOOCs also have a great impact on higher education tuition (Dennis 2012;Yuan & Powell 2013;Iqbal et al 2014;León-Urrutia et al 2016, 2018.…”
Section: Language Massive Open Online Courses (Lmoocs)mentioning
confidence: 99%
“…More specifically, Keller's model proved helpful to check the degree of motivation raised by different technological resources amongst students. Examples are: videogames [62]; the inclusion of video in e-learning learning sessions [63]; audio podcasts [64]; Massive Open Online Courses [65,66]; or AR [67][68][69].…”
Section: Information Collection Instrumentsmentioning
confidence: 99%
“…Rapidly changing IT brings society as a whole and education in particular, both new benefits and additional complications. In this regard, new approaches to education, greater use of IT facilities, greater involvement of students are needed [ Ramírez-Montoya, et al 2017-Leon-Urrutia, et al 2018.…”
Section: Resultsmentioning
confidence: 99%